PENERAPAN KURIKULUM BERBASIS STANDAR KOMPETENSI LULUSAN DI SDN PINAYUNGAN V - Dewi Zahra Camelia Hakim; Sabrina Septiani; Nurachman Ramadhan; Nabilah Zalfa; Zalfa4, Hinggil Permana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The development of education is becoming increasingly rapid and complex each year, adapting to the demands of the times. This is largely driven by the expectations of students’ parents regarding the quality and quantity of education. The Graduate Competency Standards (Standar Kompetensi Lulusan or SKL) refer to the qualifications that students must achieve, covering attitudes, knowledge, and skills, which they are expected to attain upon completing a level of education in primary and secondary schools. SKL is often recognized in schools as part of the curriculum. Through observation and interviews with school stakeholders, various factors that support or hinder the achievement of SKL can be identified. These include teacher readiness in developing SKL-based learning, the role of the school curriculum, supporting facilities and infrastructure, as well as the evaluation of student learning outcomes. This observation reveals that SKL is a key element in Indonesia’s education system, aimed at ensuring that each graduate meets the minimum competency standards in terms of attitude, knowledge, and skills. In this study, the author employs a descriptive qualitative approach to describe and analyze the implementation of SKL at SDN Pinayungan 5. The findings indicate that the implementation of SKL in Indonesia faces several challenges, one of the main issues being the inequality in educational resources. Many schools, including SDN Pinayungan 5, lack adequate facilities to support SKL-aligned learning. The author hopes that by improving the quality of education based on SKL, Indonesia can produce a competent, adaptive generation ready to face global challenges